Green Employee Behavior Model: Role of Green Attitude and Self-Efficacy - Adhariani , Fadhillah; Gunarto, Muji (International Journal of Marketing & Human Resource Research, 2026)
This study analyzes the effect of self-efficacy on green employee behavior mediated by green employee engagement and green attitude. This study is a survey of private lecturers in Indonesia who practice environmentally friendly living.  The sampling technique was purposive, with a sample of 123 respondents. Self-efficacy has a positive and significant influence on green employee behavior, mediated by green employer engagement and green attitude. This study highlights how environmentally friendly behavior, especially among lecturers, can be an essential step in addressing the problem of garbage. Teachers can serve as role models for students and staff and support sustainability initiatives on campus. Implementing Employee Green Behavior (EGB) practices within academic communities is essential to mitigate environmental impacts, as both individuals and institutions play crucial roles in sustainability. Based on this research, private colleges in Indonesia should consider implementing strategic measures to enhance faculty engagement in environmentally friendly practices. Second, green employee engagement should be improved through more structured sustainability initiatives to cultivate green attitudes, which significantly influence employees' green behavior. Third, universities need to implement environmental education programs, awareness campaigns, and incentives for environmentally friendly practices to develop pro-environmental attitudes that, in turn, encourage green employers' behavior.